2017
DOI: 10.1139/apnm-2017-0214
|View full text |Cite
|
Sign up to set email alerts
|

The repeated bout effect of traditional resistance exercises on running performance across 3 bouts

Abstract: This study investigated the repeated bout effect of 3 typical lower body resistance-training sessions on maximal and submaximal effort running performance. Twelve resistance-untrained men (age, 24 ± 4 years; height, 1.81 ± 0.10 m; body mass, 79.3 ± 10.9 kg; peak oxygen uptake, 48.2 ± 6.5 mL·kg·min; 6-repetition maximum squat, 71.7 ± 12.2 kg) undertook 3 bouts of resistance-training sessions at 6-repetitions maximum. Countermovement jump (CMJ), lower-body range of motion (ROM), muscle soreness, and creatine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 36 publications
3
51
3
Order By: Relevance
“…Furthermore, the current findings differ to those by previous studies, with impaired jumping capabilities during periods of EIMD as a result of lower body RT for 48 h post-exercise [21,32]. The discrepancy in findings between the current study, and those by others [21,32] may be due to distinct familiarity of jumping task constraints, or differences on methods of evaluation. For example, studies that have reported compromise in jump height for several days following an RT bout were moderately-trained runners [21,32], with no RT backgrounds.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the current findings differ to those by previous studies, with impaired jumping capabilities during periods of EIMD as a result of lower body RT for 48 h post-exercise [21,32]. The discrepancy in findings between the current study, and those by others [21,32] may be due to distinct familiarity of jumping task constraints, or differences on methods of evaluation. For example, studies that have reported compromise in jump height for several days following an RT bout were moderately-trained runners [21,32], with no RT backgrounds.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were unexpected, given that symptoms of DOMS have been shown to impair muscular contractility [30,31]. Furthermore, the current findings differ to those by previous studies, with impaired jumping capabilities during periods of EIMD as a result of lower body RT for 48 h post-exercise [21,32]. The discrepancy in findings between the current study, and those by others [21,32] may be due to distinct familiarity of jumping task constraints, or differences on methods of evaluation.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations